2016
DOI: 10.1186/s13148-016-0262-x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant medication during pregnancy and epigenetic changes in umbilical cord blood: a systematic review

Abstract: IntroductionEpigenetic mechanisms are important for the regulation of gene expression and differentiation in the fetus and the newborn child. Symptoms of maternal depression and antidepressant use affects up to 20 % of pregnant women, and may lead to epigenetic changes with life-long impact on child health. The aim of this review is to investigate whether there is an association between exposure to maternal antidepressants during pregnancy and epigenetic changes in the newborn.Material and methodsSystematic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…We observed small increases of 1–2% in LINE1 DNA methylation status after high-dose MTX treatment, which are are in line with previous reports in other diseases [ 9 , 23 ]. For example, in patients using selective serotonin reuptake inhibitors, global and gene-specific methylation differences of 1–5% were found to be associated with treatment response [ 23 ]. Furthermore, 5-methylcytosine levels, which is another global DNA methylation measure, differed between healthy controls and rheumathoid arthritis patients receiving MTX with 1–2% [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed small increases of 1–2% in LINE1 DNA methylation status after high-dose MTX treatment, which are are in line with previous reports in other diseases [ 9 , 23 ]. For example, in patients using selective serotonin reuptake inhibitors, global and gene-specific methylation differences of 1–5% were found to be associated with treatment response [ 23 ]. Furthermore, 5-methylcytosine levels, which is another global DNA methylation measure, differed between healthy controls and rheumathoid arthritis patients receiving MTX with 1–2% [ 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…There were an additional 15 CpG sites in cord blood associated with maternal antidepressant use that survived Bonferroni correction in Project Viva, but they were not replicated in The Generation R Study. Six prior studies of in utero antidepressant exposure and offspring DNA methylation were recently systematically reviewed by Viuff et al [20]. The authors concluded that there was no consistent association among studies and highlighted the need for untargeted epigenetic assays with external validation [20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review could not establish a clear association between use of (various classes of) antidepressant medication during pregnancy and epigenetic changes in the umbilical cord blood (Viuff et al, 2016). However, one of those studies, a genome-wide methylation study specifically addressing the role of SSRIs, identified increased methylation levels at CpG sites R e v i s e d m a n u s c r i p t 27 (where a cytosine nucleotide is followed by a guanine nucleotide in the linear sequence of bases) in the CYP2E1, EVA1 and SLMAP genes (Gurnot et al, 2015).…”
Section: Clinical Outcomesmentioning
confidence: 99%